STATE OF REMOTE CONTROL AND MANAGEMENT SYSTEMS OF TECHNOLOGICAL MODES OF WATER RESERVOIRS - Zayniddinov, Bobirjon Gofirovich (Educational Research in Universal Sciences, 2022)
In order to improve the technical condition of currently working hydrotechnical structures, develop automated systems, and improve the efficiency of the correct distribution of water resources, many scientific studies are being conducted in the world to improve the management systems of water distribution processes in reservoirs. The ongoing large-scale modernization and reconstruction programs of hydrotechnical facilities require the creation of high-efficiency remote control, that is, the automation of the process of distributing flows in reservoirs with high accuracy.